COVID-19: A Systematic Review of The Mechanisms of Injury to The Central Nervous System This Far - Loeb, Laura; Mei, Paulo Afonso (InterAmerican Journal of Medicine and Health, 2020)
2019-nCoV (COVID-19) is a single-stranded, positive-sense, encapsulated betacoronavirus, and continues to spread throughout the world. Various neurological symptoms, ranging from mild to fatal, are continuously reported, raising the importance of a better understanding of the mechanisms through which 2019-nCoV invades and harms the central nervous system (CNS). A systematic review was performed using 18 articles and it was concluded that there is strong evidence supporting the link between 2019-nCoV and nervous damage, and that there are at least three means by which it may directly enter the CNS, and three by which it may cause indirect harm to the CNS.